Packaging a Chinese “Beauty Writer”: Re-reading Shanghai Baby in a Web Context - Liu, Bin; Baer, Brian (Meta, 2017)
Based on a comparative discourse analysis of the 2001 English translation of the pioneering “beauty writer” Wei Hui’s semi-autobiographical novel Shanghai Baby and the original Chinese work (1999), this paper aims to demonstrate how the reception of non-specialist readers in the form of online book reviews is influenced by the politics of reception in the Western world as well as the translational shifts in the text. Building the investigation upon the nineteenth-century sinologist translation model that packages Chinese culture as clichéd Chineseness in addition to the Western reception model that packages Chinese women as reckless lovers and escapees from communist despotism, the study argues that largely subject to the stereotypical expectations of Western readers about the Third World culture and women, the shifts reinforcing the prevalent stereotypes in the translation overshadow the author’s original intention of speaking for a small tribe of young people exploring their unorthodox existence in China. Lastly, the study concludes with the affirmation of Shanghai Baby’s social impact on both host and source culture in an attempt to relate its significance to a global context.